Textile industry as a major source of microplastics in the environment - Branka Mušič (Global Journal of Ecology - Peertechz Publications, 2023)
This review brings together data on the impact of (micro)plastics, on the environment. Critically evaluates studies on the use of various techniques for recycling textile plastic, which is a major polluter of the environment. In this review, let's focus a bit more on industrial waste in the textile industry since it would be easiest possible to capture and recycle it again. We also discuss LCA studies, bottlenecks, and future perspectives, for a lower impact on the environment. The main challenges which make further recycling progress difficult are discussed, such as the lamination of textile fibers with metal, new textile fibers that appear as a result of rapid development, the difference in the density of textile fibers, low recycling efficiency, etc. Finally, the possible uses of more environmentally friendly polymers are shown, which can be an alternative to the current synthetic polymers.  The results of the literature review showed that for the development of a sustainable textile industry, which would mitigate the impact of microplastics on the environment, from a long-term perspective, the integration of more intensive, complex decisions into the business models of manufacturing companies is necessary. The environmental consequences will be even more intense due to the massive releases of textile microfibers into the environment and excessive accumulation, therefore, in order to achieve the specific goals of sustainable development, a reduction in the production of microplastics is first required, which is only possible with a global partnership of all countries to achieve a specific goal on a global level.